Attitudes of secondary school students towards physical education and sports lesson in terms of various variables - Merve Imamoglu; Tulin Atan (Türk Spor ve Egzersiz Dergisi)
The purpose of this study is to analyze the attitudes of students towards the lesson of physical training and sports in schools and to analyze the situations which are effective on these. A total of 129 (63 girls, 66 boys) between the ages 11 and 14 (13.01 ± 1.80 years) studying at Secondary School participated in the study. Physical Training and Sports Attitude Scale which was 5-Likert type with 24 items, 12 positive and 12 negative and developed by Demirhan amp; Altay was used to measure the students’ attitudes. Personal information form includes information such as the students’ grades, genders, place of residence, level of education of parents, family’s level of income and number of siblings. No significant difference was found in scores of attitudes towards physical education and sports lesson in terms of their grades, gender, place of residence (p gt;0.05). No significant difference was seen in students’ attitudes in terms of parents’ levels of education and number of siblings (p gt;0.05). As a conclusion grade, gender, place of residence, parents’ level of education, level of income and number of siblings did not affect the physical education and sports lesson attitude scores of secondary school students who are between the ages 11 and 14 years.